Costs associated with road crashes in the WHO European Region. (1st March 2011) - Zambon, F; Sethi, D; Racioppi, F
Abstract : Aim and Methods: To assess the economic impact of road crashes the World Health Organization in 2008 collected information on the economic costs of road traffic injuries and on the expenditure on road safety. Results: 55% of the surveyed 49 countries in the WHO European Region provided estimates for the economic costs of road traffic injuries. For countries using the gross output methodology (therefore including property damage, healthcare and administration costs, absence from work and long-term disability or death) the average economic burden due to road crashes per person ranges from 10 to 1300. Expressed as proportion of the Gross Domestic Product-GDP, the estimated economic burden ranges from 0.4% to 3.1% of GDP, being higher for high-income countries. With regard to national funds specifically devoted to the implementation of national strategies on road safety, on average countries in the WHO European Region invest 8.5 per person. However, countries like Spain, Norway and France invest up to four times more on road safety than the European average. A comparison between the expenditure on national road safety strategies and the costs of road crashes shows that the economic costs of road traffic injuries are up to 70 times higher than the expenditure on safety. Conclusion: In spite of the methodological limitations, it can be concluded that more countries need to conduct standardised studies on national costs of road crashes. Such estimates can be used to advocate for more resources and to promote more investments in road safety.